Institutional aspects of the improvement of the management in the mineral and raw complex - Yu. B. Vinslav; S. V. Lisov (Известия высших учебных заведений: Геология и разведка)
A conclusion has been justified, that the institutional norms and rules existing for the mineral resources use relations, extremely poorly affect industrial and innovative aspect of the activity of the mineral and raw complex (MRC). Actually these norms and rules preserve a hypertrophied export and raw orientation of activity of the MRC enterprises. Perspective development of the domestic MRC has to be based on the considering of the requirements of a set of the institutional norms relating as directly to the sphere of production and reproduction of mineral raw materials, and to the industrial innovative regulation assuming transition to the economy of the highest technological ways. The purpose, tasks, the basic principles of the industrial policy in relation to MRC’s activity have been formulated. A methodical approach to the development of the strategic courses of the development of the geological sector has been offered. Suggestions for the improvement of the mechanisms of staffing of the sphere of mineral resources use have been given.